Randomized phase II study of nintedanib with or without pirfenidone in patients with idiopathic pulmonary fibrosis who experienced disease progression during prior pirfenidone administration. Issue 22 (3rd June 2022) - Ikeda, Satoshi; Sekine, Akimasa; Baba, Tomohisa; Kato, Terufumi; Katano, Takuma; Tabata, Erina; Shintani, Ryota; Yamakawa, Hideaki; Oda, Tsuneyuki; Okuda, Ryo; Kitamura, Hideya; Iwasawa, Tae; et al.
Abstract: Introduction: A subgroup analysis of the CAPACITY and ASCEND trials showed that pirfenidone use beyond disease progression reduced the risk of subsequent forced vital capacity (FVC) decline and death. Our study aimed to compare the efficacy and safety of nintedanib with or without pirfenidone for patients with idiopathic pulmonary fibrosis (IPF) who experienced disease progression during previous pirfenidone therapy. Methods: In this randomized, open-label, selection design phase II trial, patients with IPF and a ≥5% relative decline in FVC within 6 months of the pirfenidone administration period were randomly assigned to nintedanib (switch group) or nintedanib plus pirfenidone (combination group). The primary endpoint was the incidence of a ≥5% relative decline in FVC or death during the first 6 months. Results: Only 7 patients were enrolled (4 in the switch group and 3 in the combination group). Although the switch group continued with nintedanib for 1 year or more, 2 patients (66.7%) in the combination group discontinued nintedanib within 6 months due to severe adverse events. Given the slow case registration and safety concerns in the combination group, the trial was terminated without extending the registration. The incidence of a ≥5% relative decline in FVC during the first 6 months was 50.0% in the switch group and 66.7% in the combination group. There were no deaths during the observation period. Conclusions: Clinical trials verifying the use of pirfenidone after disease progression in IPF may be difficult to enroll patients. Definitive conclusions on both safety and efficacy cannot be drawn from the results of this study alone. Trial registration: UMIN Clinical Trial Registry; registration number, UMIN000019436; date of first registration, 21/10/2015; https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000022471 .